2012
DOI: 10.1089/gtmb.2011.0222
|View full text |Cite
|
Sign up to set email alerts
|

C677T and A1298C Polymorphisms ofMTHFRGene and Their Relation to Homocysteine Levels in Turner Syndrome

Abstract: The results suggest that the C677T and A1298C polymorphisms of the MTHFR gene are not related to homocysteine levels in Brazilian patients with TS, despite the differential distribution of the mutated allele C (A1298C) in these patients. Further studies are needed to investigate the possible genetic interaction with homocysteine levels in TS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
1
13
1
5
Order By: Relevance
“…The A1298C polymorphism seems relatively prevalent in the Iranian population and the frequency of the 1298CC genotype (16.4%) in our population is much higher than that reported for Portuguese (5.98), American (7.9%), Brazilian (5%), Poland (4%) and Bahraini Arab (4%) populations [28,31,[33][34][35]. However, the frequency of the 1298CC genotype in our population is lower than that reported in Pakistan (23%) and Lebanon (23.9%) populations [30,36].…”
Section: Discussioncontrasting
confidence: 67%
“…The A1298C polymorphism seems relatively prevalent in the Iranian population and the frequency of the 1298CC genotype (16.4%) in our population is much higher than that reported for Portuguese (5.98), American (7.9%), Brazilian (5%), Poland (4%) and Bahraini Arab (4%) populations [28,31,[33][34][35]. However, the frequency of the 1298CC genotype in our population is lower than that reported in Pakistan (23%) and Lebanon (23.9%) populations [30,36].…”
Section: Discussioncontrasting
confidence: 67%
“…Estrogen deficiency in TS, due to X chromosome monosomy, could be a possible cause of hyperhomocysteinemia. Most of our patients were on HRT in contrast to previous findings [22]. Hcy levels were significantly decreased and below the cutoffs, confirming previous findings that report a positive association between Hcy levels and HRT [34].…”
Section: Discussionsupporting
confidence: 89%
“…Homozygote (TT genotype) individuals produce a thermolabile enzyme, which results in a 40–50% decreased activity, affecting the remethylation step and causing mild hyperhomocysteinemia [21]. In our patients, tHCy levels did not differ among subjects with or without mutation, suggesting the importance of vitamin supplementation despite the genetic profile, as the involvement of chromosomal imbalances on MTHFR is not excluded [22]. …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Oliveira et al suggested that the A1298C polymorphism of the MTHFR gene is not associated with Hcy levels in Brazilian patients with Turner syndrome. [38] Hanson et al also found that the A1298C polymorphism was not associated with either fasting or post-methionine load Hcy in vascular disease. [39] However, Zappacosta et al [40] found that Hcy was higher in those with the wild type and lower in those who were homozygous.…”
Section: Discussionmentioning
confidence: 99%